Changing structure of employment in Europe: Polarization issue - Radek Náplava (Review of Economic Perspectives, 2019)
In recent years, labor markets have experienced a polarization phenomenon, with the rise of low-skill and high-skill workers, and a decline in the number of middle-skill workers. The polarization of the labor market has been most often investigated in the US, UK, and some European countries. This paper shows the changes in the employment structure in all EU countries between 2008 and 2017. Attention is also paid to the Czech Republic and change during 1993 and 2017. The added value of the article lies in two factors. The first is the division of skills by industry in which the worker is located and not by occupational classification, the second is an explicit view of the Czech Republic. The results provide some evidence about the polarization of the labor market in twenty-one EU countries. Results imply polarization also in the Czech Republic during a longer period, because the number of high-skilled and low-skilled workers increased by 6.63 p. p. and by 1.16 p. p. respectively, at the expense of middle-skilled workers.
Keywords: J21; J23; 330; polarization; labor market; employment; skills